Fifteenth-Century Liturgical Music IV Early Masses and Mass-Pairs - Curtis, Gareth (London Stainer and Bell, 2001)
Movements from incomplete cycles and pairings both scribal and scholarly constitute a volume of English Mass music from the period after the Old Hall Manuscript. The repertory is presented in a style of transcription new to the series and intended to convey the essential nature of this freely flowing yet mensurally disciplined music. Works by John Benet, Bloym, Driffelde, Leonel Power and Anon are included.
Keywords: 15th Century (1401-1500); Mass; United Kingdom